An analysis and successful benchmarking of the Chapman-Enskog-like (CEL) continuum kinetic closure approach algorithm in NIMROD - Joseph R. Jepson; Chris C. Hegna; Eric D. Held; Carl R. Sovinec; J. Andrew Spencer; Eric C. Howell (Computer Physics Communications, 2025)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Maternal Ethanol Exposure Acutely Elevates Src Family Kinase Activity in the Fetal Cortex - Dandan Wang; Brian W. Howell; Eric C. Olson (Molecular Neurobiology, 2021)
Fetal alcohol syndrome (FAS) is characterized by disrupted fetal brain development and postnatal cognitive impairment. The targets of alcohol are diverse, and it is not clear whether there are common underlying molecular mechanisms producing these disruptions. Prior work established that acute ethanol exposure causes a transient increase in tyrosine phosphorylation of multiple proteins in cultured embryonic cortical cells. In this study, we show that a similar tyrosine phosphorylation transient occurs in the fetal brain after maternal dosing with ethanol. Using phospho-specific antibodies and immunohistochemistry, we mapped regions of highest tyrosine phosphorylation in the fetal cerebral cortex and found that areas of dendritic and axonal growth showed elevated tyrosine phosphorylation 10 min after maternal ethanol exposure. These were also areas of Src expression and Src family kinase (SFK) activation loop phosphorylation (pY416) expression. Importantly, maternal pretreatment with the SFK inhibitor dasatinib completely prevents both the pY416 increase and the tyrosine phosphorylation response. The phosphorylation response was observed in the perisomatic region and neurites of immature migrating and differentiating primary neurons. Importantly, the initial phosphotyrosine transient (~ 30 min) targets both Src and Dab1, two critical elements in Reelin signaling, a pathway required for normal cortical development. This initial phosphorylation response is followed by sustained reduction in Ser3 phosphorylation of n-cofilin, a critical actin severing protein and an identified downstream effector of Reelin signaling. This biochemical disruption is associated with sustained reduction of F-actin content and disrupted Golgi apparatus morphology in developing cortical neurons. The finding outlines a model in which the initial activation of SFKs by ethanol has the potential to disrupt multiple developmentally important signaling systems for several hours after maternal exposure.

A dry future for the Everglades favors invasive herpetofauna - Hunter J. Howell; Giacomo L. Delgado; Alyssa C. Wood; Leila M. Thompson; Eric A. Cline; Christopher A. Searcy (Biological Invasions, 2021)

Ethanol Exposure Transiently Elevates but Persistently Inhibits Tyrosine Kinase Activity and Impairs the Growth of the Nascent Apical Dendrite - Dandan Wang; Joshua Enck; Brian W. Howell; Eric C. Olson (Molecular Neurobiology, 2019)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Preparing for climate change in Washington State - Lara C. Whitely Binder; Jennifer Krencicki Barcelos; Derek B. Booth; Meriel Darzen; Marketa McGuire Elsner; Richard Fenske; Thomas F. Graham; Alan F. Hamlet; John Hodges-Howell; J. Elizabeth Jackson; Catherine Karr; Patrick W. Keys; et al. (Climatic Change, 2010)